Orthopedics & Sports Medicine - Edouard P; 2; 3; Dandrieux P-E; 4; Chapon J; Prince C; 6; Charpy S; 2; Bruneau A; Navarro L; et al. (Deutsche Zeitschrift für Sportmedizin)
Problem: Injuries in athletics are common and may lead to restrictions in athletics participation and performance. We thus aimed to describe the epidemiology (prevalence, incidence, burden, characteristics) of injuries self-reported by the athletes (injury complaint leading to participation restriction (ICPR)) in athletics athletes) over one athletics season. Methods: For this study, we used data from the PREVATHLE randomized controlled trial and only from athletes of the control group who provided 100% of the weekly responses. On a weekly basis, we collected individual information via a questionnaire on the preceding week: number of hours of training and competition, and any ICPR (circumstance, mode of onset and location). The primary outcome was ICPR.Results: Overall, full data sets were available for 100 athletes. One hundred twenty-seven ICPR were reported from 65 athletes over the season, corresponding to a prevalence rate of 65 ICPR per 100 athletes (95%CI: 55.7-74.3). The incidence rate was 8.3 ICPR per 1000h (95%CI: 6.9-9.7), the overall injury burden was 285.6 (SD=619.6) days with an ICPR per 1000h, and the time before the first ICPR was 12.4 (SD=10.4) weeks. Most acute injuries occurred at the ankle (9.4%), while most overuse injuries occurred at the lower leg (15.0%).Conclusion: This present epidemiological study describes in detail the epidemiology of ICPR in athletics athletes over one whole athletics season, representing an additional piece to better understand the extent of injury problem in athletics.Key Words: Musculoskeletal Pathologies, Prevention, Monitoring